Soil Structure Evaluation Across Geologic Transition Zones Using 2D Electrical Resistivity Imaging Technique - Anukwu, Geraldine C; Adebara, A. F.; Abodunrin, T. K.; Iwakun, A. P. (Journal of Geoscience, Engineering, Environment, and Technology, 2017)
This study utilizes the electrical resistivity values obtained using 2-D Electrical resistivity imaging (ERI) technique to evaluate the subsurface lithology across different geological units. The primary objective was to determine the effect of subsurface lithology on the integrity of a road pavement, which had developed cracks and potholes at various locations. The dipole-dipole configuration was utilized and a total of nine traverses were established in the study area, whose geology cuts across both the basement and sedimentary complexes. The inverted resistivity section obtained showed significant variation in resistivity along established traverses and also across the different rock units, with the resistivity value ranging from about 4 ohm-m to greater than 7000 ohm- m. The lithology as interpreted from the resistivity section revealed the presence topsoil, clay, sandy clay, sand, sand stones/basement rocks, with varying vertical and horizontal arrangements to a depth of 40m. Results suggest that the geologic sequence and structure might have contributed to the observed pavement failure. The capability of the 2D ERI as an imaging tool is observed, especially across the transition zones as depicted in this study. The study further stressed the ability of this technique if properly designed and implemented, to be capable of providing a wealth of information that could complement other traditional geotechnical and geologic techniques.